(untitled) (Al-Academy, 2022)
Modern critical theories revealed polemical views about the reality of the existence of communication - as a necessity for building a deliberative discourse - in the theater or not. To the theory of communication with all the conditions it imposes on thinking, interaction, and emancipation of selves in different contexts.Therefore, the current research included four chapters, the first chapter dealt with the research problem, which was represented in (the philosophy of sensory and physical communication in theatrical performance), and the first chapter included the importance of the research, its goal and its limits, and ended with defining the terminology, and the second chapter included (theoretical framework) the first topic (philosophical communication), The second topic (communicative theory, its elements and theatrical formats), while the third chapter included a sample and research tool, research and analysis method for a play exhibition (No What Happens), and the fourth chapter included the results of the analysis and the most important conclusions, then referrals and a list of sources